PROJECTIVE NORMS AND CONVERGENCE OF NORM-ATTAINABLE OPERATORS - okelo, benard; Ongati, Omolo; Karieko, Obogi Robert (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
Let H be an innite dimensional complex Hilbert space and B(H) the algebra of all bounded linear operators on H. We establish norm-attainability of operators via projective tensor norm. Moreover, we give results on the convergence of norm-attainable operators.